Novel and divergent viruses associated with Australian orchid-fungus symbioses - Ong, J.; Li, H.; Sivasithamparam, K.; Dixon, Kingsley; Jones, M.; Wylie, S. (Elsevier Science BV, 2018)
© 2017 Elsevier B.V. Terrestrial orchids represent a symbiotic union between plants and mycorrhizal fungi. This study describes the occurrence and nature of viruses associated with one population of wild Pterostylis sanguinea orchids, including their fungal symbionts, over two consecutive years. A generic sequencing approach, which combined dsRNA-enrichment from plant and mycelial tissues, random amplification and high throughput shotgun sequencing was used to identify novel viruses. The majority of the virus-like sequences represent partial genomes, and their identification is based solely on de novo assembly of sequencing data. In orchid leaf tissues we found three isolates of a novel totivirus and an unclassified virus; both resemble fungus-infecting viruses. Two isolates of Ceratobasidium sp that were isolated from orchid underground stems contained at least 20 viruses, 16 of which were previously described as alphapartitiviruses and betapartitiviruses. A novel hypovirus and a mitovirus were genetically distant from existing members of the genera and did not readily fit into recognised subgroups.